Neoliberalism and the changing direction of schools: an edupreneurial leadership approach - Larey, Desireé Pearl (Emerald, 2024)
𝗣𝘂𝗿𝗽𝗼𝘀𝗲 This qualitative study discusses the importance of effective leadership practices in connecting the macro-, meso-, and micro-contexts in which school leaders operate, considering the colonial and apartheid history of South Africa and the current era of neoliberal philosophies by exploring the degree to which school leaders in historically disadvantaged schools in Western Cape Province use an edupreneurial approach to steer their schools in new directions. The school leaders, especially in historically disadvantaged Colored schools, are expected to be more autonomous and accountable for making the school environment conducive to performance standards and improved learning results. The study uses an edupreneurial leadership approach as a theoretical lens to explore entrepreneurial agency, together with the educational leadership approach of school principals as a consequence of neoliberal policies. 𝗗𝗲𝘀𝗶𝗴𝗻/𝗺𝗲𝘁𝗵𝗼𝗱𝗼𝗹𝗼𝗴𝘆/𝗮𝗽𝗽𝗿𝗼𝗮𝗰𝗵 This study focuses on secondary schools in historically Colored communities in Western Cape Province through semi-structured interviews with four purposively selected school principals and four teachers from four different schools in the Western Cape Province. 𝗙𝗶𝗻𝗱𝗶𝗻𝗴𝘀 Education and training programs should focus on cultural values and practices to enhance the efficacy of these schools. Furthermore, an entrepreneurial mindset and spirit are aspects that can be encouraged in a culturally sensitive manner. The edupreneurial leadership approach in developing countries has a distinctive nature. 𝗢𝗿𝗶𝗴𝗶𝗻𝗮𝗹𝗶𝘁𝘆/𝘃𝗮𝗹𝘂𝗲 This study contributes to forging an understanding of how neoliberal trends influence school leadership practices in developing countries, especially the leadership work of school principals across public schools in the Western Cape Province in South Africa.
Keywords: Apartheid; Colored people; Edupreneurial leadership; Leadership practices; New public management; Neoliberalism; School leadership; South Africa